PENGARUH PRODUK DOMESTIK BRUTO DAN SBI TERHADAP PENERIMAAN PAJAK DI INDONESIA - Rahmanta Ginting (Quantitative Economics Journal, 2012)
The research to analyse effect net domestic product and SBI on tax revenue in Indonesia with independent variables  net domestic product and SBI also dependent variables tax revenue. Data is a time series between 1981 - 2010 with ordinary least square (OLS) and the model of formula used is multiply linier regression.  The research result shows that net domestic product gives a positive effect and significant on tax revenue in Indonesia on 99% level. While SBI has a negative effect and significant on tax revenue in Indonesia on 90% level.